Dampak Perbedaan Antara Laba Akuntansi dan Laba Fiskal (Boot Tax Differences) serta Faktor yang Mempengaruhi Perilaku Persisntensi Laba Perusahaan Manufaktur di Indonesia - Almatius Marsudi; Lim Thingthing (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2020)
The purpose of this study is to analyse empirical evidence of the effect of differences between accounting earnings and fiscal profits (book tax differences), operating cash flows and accrual amounts on the persistence behavior of corporate earnings. This study uses data from manufacturing companies in the Indonesian stock exchange during the period 2015 to 2017. The sample selection is have purposive sampling method and obtained a sample of 71 manufacturing companies in Indonesia that have met the research criteria. Data is analyzed with multiple regression to have the effect of independent variables on earnings persistence. The results showed that differences in accounting profit and taxable income and the magnitude of accrual did not affect earnings persistence while operating cash flow had an effect on earnings persistence.